The Welfare Effects of Mobile Internet Access - Evidence from Roam-Like-at-Home - Martin Quinn; Miguel Godinho de Matos; Christian Peukert (Center for Economic Studies and ifo Institute (CESifo), 2022)
We evaluate the welfare effects of the Roam-Like-At-Home regulation, which drastically re-duced the price of accessing the mobile internet for EU residents when traveling abroad in the European Economic Area. Estimates from individual-level usage data suggest that consumer surplus increased by 2.77 EUR/user/travel day. A decomposition shows the heterogeneous impact of the regulation on different user segments. We estimate that around half of the gains stem from a reduction in deadweight loss, i.e., new users accessing the mobile internet. We further show that the impact of the regulation varies with usage intensity abroad and at home, by the nature of the trip (leisure vs. business), and by content type. We discuss implications for content providers and other policy areas such as net neutrality.
Keywords: L96; L51; O33; D62; 330; Telecom; mobile data; roaming; regulation; consumer surplus